Jumping ship : from the world of corporate Australia to the heart of social investment - Traill, Michael (Hardie Grant Books, 2016)
As an ambitious, competitive kid from a public school, who grew up in a country town in Victoria, Michael Traill converted privileged education opportunities in the hallowed halls of Melbourne University's Trinity College and the Harvard Business School into a highly paid and successful career at Macquarie Bank, often called the millionaire's factory. But a career devoted to money-making was never going to satisfy Michael's deeper yearnings: his passion for social justice; his determination to make the world a better place. So at the peak of his career and only in his early forties he decided to leave merchant banking behind. His vision was to bring the rigour and hard-headedness of the world of finance to the world of philanthropy and social entrepreneurship. This book tells the candid and inspiring story of the journey that took him from a modest small town in Morwell to the millionaire.s factory and then on to founding a unique Australian non-profit success story. This led to being a key architect, along with a group of financial high-fliers, who found a way to run a multi-million dollar business devoted entirely to the creation of social good rather than profit. In the process they were at the forefront of addressing social disadvantage and reshaping the Australian non-profit landscape.